Evaluation of current gene pool of Kholmogor and Black-and-white cattle breeds based on whole genome SNP analysis - A. V. Dotsev; A. A. Sermyagin; A. V. Shakhin; I. A. Paronyan; K. V. Plemyashov; H. Reyer; K. Wimmers; G. Brem; N. A. Zinovieva (Вавиловский журнал генетики и селекции)
Conservation of local cattle genetic resources is an important strategy for achieving Russia’s food security. During last decades, in the Russian Federation, local livestock populations were either crossbred or replaced by highly productive imported breeds, which led to a loss of the major part of original breeds identities. The objective of our study was to identify genetic differences between the populations of Kholmogor and Black-and-white cattle with varying degrees of admixture with the Holstein breed. The aforementioned breeds were studied using their whole-genome single nucleotide polymorphism (SNP) genotypes. The Kholmogor breed was subdivided into three groups: purebred (KHLM, n = 3), admixed with Holsteins (KHLM-HLST, n = 4) and representatives of old-type breed (KHLM-INTA, n = 15). Blackand-white was subdivided into four groups: purebred (BLWT, n = 9), with a low (BLWT-75, n = 8) and a high (BLWT-HLST, n = 10) level of admixture with Holstein, and represented by archival samples from the 1970s and 1980s (BLWT-OLD, n = 15). The Holsteins genetic profiles (HLST, n = 27) were taken as a comparison group. PLINK 1.07, Admixture 1.3, SplitsTree 4.14.6 and R package StAMPP were used to infer genetic relationship between the studied groups. After quality control, 29 688 SNPs were selected for analysis. Multidimensional scaling (MDS), Admixture analysis and a dendrogram constructed using the Neighbor-Net method, revealed the presence of three clusters belonging to the Kholmogor, Black-and-white and Holstein breeds. The first one included KHLM and KHLM-INTA, the second – BLWT and BLWT-OLD, and the third – HLST, KHLM-HLST and BLWT-HLST. The BLWT-75 samples were placed between HLST and BLWT. Thus, our results showed that currently the populations of native cattle breeds with valuable genotypes still exist. The populations with a high level of admixture with Holsteins could be considered neither as the Kholmogor nor as Blackand-white breeds, and would rather be referred as the Holstein breed of local breeding.